Transtornar-se como ato clínico: uma contraficção de gêneros e sexualidades dissidentes - Checa, Maria Eduarda Parizan (2021)
This writing is about clinical listening in its decolonizing power over the heterosexual and cisgender neurosis. Herein I write in the first person, twisting the self-fictional meaning which could be attributed to this text, transforming it into a conter-fiction, as an exercise of fighting against the compulsory hetero-cis-normative fiction in me, both as a psychologist and as a patient. If the psychopathological discourse sickens and annihilates those who do not submit to the sexual difference regimen, it is in that very place of illness - as a political territory - that resides the importance of affirming itself micropolitically and macropolitically. To become disorded as a clinical act is to assume the psychological disorder, the diagnosis, from an ethical, clinical and queer place of subjectivity. Once psychopathologized, hetero-cis-dissident subjectivities are able to find a combat tool that is, at the same time, an ethical, aesthetic and political power: the removal of heterocis neurosis in themselves